Peningkatan Kesejahteraan Pengrajin Gula Nira Kelapa melalui Kualitas Pola Tanam Kelapa, Diversifikasi Olahan Produk, Digital Marketing dan Kemasan Produk di Desa Sendang Kecamatan Donorojo Kabupaten Pacitan - Widayanti, Rochmi; Widiastuti, Libria; Sutianingsih, Sutianingsih (LPPM ITB AAS Indonesia Surakarta, 2024)
Sendang Village is one of the villages in the Donorojo District of Pacitan Regency. In addition to having agricultural land and plantations, Sendang village has a beach tourist attraction with high potential for development. Agricultural results are primarily obtained from the yields of plantations and community forestry. One of the commodities utilized by farmers in Sendang is the traditional craft of coconut sap sugar, which has been passed down through generations and remains traditional in both its production process and marketing. The issues faced by coconut sap artisans include the limited yield of harvested sap, the production process still being traditional with the use of large circular blocks, a lack of diverse product processing, and marketing being restricted to local areas with unappealing packaging. The Community Partnership Program (PKM) aims to help solve the problems faced by coconut sap craftsmen in Sendang Village. The program consists of a workshop on the planting patterns of green coconuts as a source of coconut sap, training in simple financial management, and training in the production of processed products from coconut sap in small forms and powdered sugar. After that, it continued with digital marketing training or an introduction to online marketing media, as well as practical exercises using more hygienic and attractive product packaging. The results of this community service activity are expected to increase income through the production of a large quantity of sap, with a variety of products that can penetrate a wider market share through online media and hygienic, practical packaging. Keyword: Coconut Nira, Simple Bookkeeping, Digital Marketing, Product Processing Diversification, Product Packaging